2019
DOI: 10.1371/journal.pone.0210721
|View full text |Cite
|
Sign up to set email alerts
|

Does caste determine farmer access to quality information?

Abstract: This paper explores the social inclusiveness of agricultural extension services in India. We estimate the probability and frequency of farmers’ access to extension services and resulting changes in crop income across different caste groups. The literature suggests that caste-based social segregation manifests in various spheres of life, and perpetuates economic inequality and oppression. An econometric analysis of nationally-representative data from rural India verifies this with respect to the agricultural se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 62 publications
(63 reference statements)
0
30
0
Order By: Relevance
“…However, SC cultivators suffer exclusion from the public extension system in general and to the veterinary department in particular. In a recent article Krishna et al (2019) have shown that the socially marginalised castes, particularly the SCs and tribes are disadvantaged in terms of accessing agricultural extension services. This definitely not only affects their awareness and access to better marketing opportunities but also limits their knowledge about good breeds of animals, finances for the purchase of animals, use of better animal feed and other inputs, etc.…”
Section: Discussionmentioning
confidence: 99%
“…However, SC cultivators suffer exclusion from the public extension system in general and to the veterinary department in particular. In a recent article Krishna et al (2019) have shown that the socially marginalised castes, particularly the SCs and tribes are disadvantaged in terms of accessing agricultural extension services. This definitely not only affects their awareness and access to better marketing opportunities but also limits their knowledge about good breeds of animals, finances for the purchase of animals, use of better animal feed and other inputs, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, there are also means such as extension strategies or approaches linked to specific values that seem to be part of extension quality but cannot be expressed in terms of results. Some examples are the implementation of culturally appropriated and socially inclusive interventions and the use of participatory processes or gender sensitivity (Trigo et al, 2013;Krishna et al, 2019). Thus, the quality of RE&AS cannot be reduced only to reaching desired goals but should also include socially acceptable interventions and technically pertinent recommendations.…”
Section: Quality As Clients' Satisfaction or As Results?mentioning
confidence: 99%
“…In India, farm households can be divided into two main social categories: general caste, and scheduled caste and tribes. The “general caste” is regarded as upper caste and the “scheduled caste and tribes” as underprivileged in several aspects (Krishna, Aravalath, & Vikraman, 2019). The result shows that the general caste dummy is positive and significant for Model A (overall), Model B (Bihar), and Model C (Haryana), signifying that households belonging to the general caste category are more likely to adopt CSA.…”
Section: Findings Of the Studymentioning
confidence: 99%